1983
DOI: 10.5453/jhps.18.113
|View full text |Cite
|
Sign up to set email alerts
|

Stable iodine contents in human milk related to dietary algae consumption.

Abstract: Studies were carried out to investigate iodine contents in human milk with relation to dietary algae consumption by nursing women and to estimate stable iodine intake by breast-fed babies. The iodine contents in human milk collected from the Tokai-mura area showed a fairly wide variation ranging from 80 to 7,000 ig/l, though the highest frequency was around 150g/l.It was observed that high contents were closely related to the intake of tangle (Konbu), Laminariaceae, specifically tangle stock and/or tangle shav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…In our study the median (reference range) of BMIC was 176 (111, 355) µg/kg in the early postpartum period and 135 (82,238) µg/kg at one postpartum month respectively consistent with the results of this large study [37]. In Japan several studies on BMIC values have been reported since 1968 [42][43][44][45][46]; however, except for one report [43] their sample sizes were small and the values were highly variable. BMIC was measured by using Sandell-Kolthoff reaction [43,45] or ICP-MS [46] or others [42,44].…”
Section: Breast Milk Iodine Concentrationsupporting
confidence: 88%
“…In our study the median (reference range) of BMIC was 176 (111, 355) µg/kg in the early postpartum period and 135 (82,238) µg/kg at one postpartum month respectively consistent with the results of this large study [37]. In Japan several studies on BMIC values have been reported since 1968 [42][43][44][45][46]; however, except for one report [43] their sample sizes were small and the values were highly variable. BMIC was measured by using Sandell-Kolthoff reaction [43,45] or ICP-MS [46] or others [42,44].…”
Section: Breast Milk Iodine Concentrationsupporting
confidence: 88%
“…Regular consumption of a diet rich in seaweeds, in these countries, has been related to extremely low incidence of breast cancer due to high availability of iodine in the diet (Drum, 2003). A remarkable increase in the iodine content in the breast milk of Japanese (Muramatsu, Sumiya, & Ohmono, 1983) and Korean (Moon & Kim, 1999) lactating mothers consuming algae and seaweeds has also been reported. In a study on lacto-vegetarians who were directed to avoid iodized salt, seaweed and iodine-containing processed foods and beverages, it was reported that iodine intake was low (Remer, Neubert, & Manz, 1999).…”
Section: Addition To Food As a Source Of Dietary Iodinementioning
confidence: 89%
“…Breast-milk iodine concentrations are higher in nonendemic than in endemic goiter regions (219)(220)(221)(222), in areas where iodophores are used for sanitizing in dairy farming (223,224), and in countries with salt iodization (224,225). In areas where maternal iodine intake is exceptionally high due to the consumption of seaweed and algae, breast-milk iodine concentrations are as much as 10 times higher than that reported in other regions (226,227). Maternal iodine supplementation is also effective at increasing breast-milk iodine concentrations (228,229).…”
Section: Iodinementioning
confidence: 98%